LEMBAGA PENYELEGGARA PEMILIHAN UMUM DALAM PEMBENTUKAN BADAN AD HOCK DI KABUPATEN KONAWE - Crisbiantoro, Jefry; Asbar, Ijang; Sam Liambo, Haldin (Lafadz Jaya Publisher, 2023)
Indonesia, which is a democratic country, elections are an instrument to exercise people's sovereignty. In order to produce a quality election, a professional institution that manages elections is needed. Election organizers recruit staffAd Hock for Elections 2024. At least there is a AgencyAd Hock at the sub-district, village and sub-district levels of 28 sub-districts scattered in Konawe Regency. Like a pyramid, the further down a row, then it gets bigger and wider. While the knowledge and skills of implementation are mandatory equalized. The standard of governance for the implementation and supervision of elections must be owned by everyone election administrators at all levels. This is the main key to realizing elections with integrity future. However, it cannot be denied, the capacity building of election organizers is especially important levelAd Hock, namely sub-districts to polling stations, are very limited. Amount technical guidance and outreach are determined by budget availability and implementation schedule. In the end, the limited amount and time were not followed by all stakeholders. Even the simultaneousness of the upcoming elections is increasingly narrowing the space for capacity building. So appointed, election administratorAd Hock directly implement and supervise the due stages its formation was carried out very close to the work that immediately had to be done, By therefore, the recruitment of election organizersAd Hock be the key to the realization of the organizers who are truly qualified and have integrity and adequate capacity. Selection is really carried out to attract candidates who have the appropriate knowledge and skills with the provisions of the law, have a personality with integrity and have a soul strong service to all parties with diverse backgrounds. Three Paths of Recruitment election administratorAd Hock is an important concern for the KPU and Bawaslu at this time. integrity election administratorAd Hock through a selection that will be carried out by the KPU and Bawaslu. That is full attention to integral fulfillment of requirements, openness and massive outreach during the recruitment process and the involvement of all parties to recruit the best sons and daughters in carrying out and supervising the electoral process. Election organizer candidateAd Hock confirmed never take sides, let alone commit fraud. In addition to of course remain open and establish intensive communication with anyone, not necessarily shut down at will. As for the conditions have the ability and expertise related to the administration of elections, state administration, party and election supervision is confirmed through a written test that concentrates on authorities, obligations, main tasks and functions as an ad hoc organizer. All written tests relating to how to carry out the stages technically to measure the ability of para candidates so that they get an idea of their readiness when directly carrying out the stages elections quickly.